LEARNING MATERIALS INNOVATION IN THE CONTEMPORARY HISTORY OF THE WORLD WITH LOCAL HISTORY - Pradata Ardi Saputro (Universitas Negeri Yogyakarta, 2023)
Education has developed along with the progress of the times. Efforts are needed to improve the quality of education at this time. Teachers as central figures in the learning process must be able to improve their quality in teaching and learning activities. Learning innovation in the learning process needs to be done to realize quality education. With learning innovations, it can create a conducive atmosphere in teaching and learning activities so that students can gain knowledge to the fullest. Learning material is one of the important elements in the learning process. Materials related to local history will attract students' attention and interest to learn history. This study aims to innovate material in history learning in high school in order to increase student interest in learning. This is motivated by the declining interest of students in studying history, especially in contemporary world history material. Low interest in learning will affect the achievement of learning objectives. The method used in this research is qualitative research by combining the results of interviews with the study of documents relevant to this research. The results of this study are (1) Knowing history learning in high school, (2) Knowing the background of students feeling bored with history learning, (3) Knowing that material innovation in contemporary world history materials can increase students' interest in learning.